Pengaruh Terapi Taubat dan Istighfar Dalam Menurunkan Kecemasan Mahasiswa - Dian Nugrahati; Qurotul Uyun; Sumedi P Nugraha (JIP (Jurnal Intervensi Psikologi), 2018)
The aim of this research is to look at the effect of taubat dan istighfar or repentance and seeking forgiveness therapy on anxiety. The subject of this research is psychology students. The research was carried out in the form of quasi-experimental, using pre-test analysis, post-test analysis, and follow-up. Before the treatment, all of the subjects were given the anxiety scale using the Beck Anxiety Inventory (BAI), in which subject with high and moderate anxiety will be used as research subjects. The data were analyzed using the T-test method to measure the significance and effect size on both variables. The results are r= 0.8 (.00< r <1.00) and p= 0.003 (p<0.05) in which shows that there is a significant effect on anxiety before and after therapy was given, and there variabilities or effects produced by the therapy. Based on this research shows that the repentance and seeking forgiveness therapy effective in lowering the anxiety level for Undergraduate students. Keywords: repentance and seeking for forgiveness therapy,  taubat dan istighfar, anxiety, undergraduate student